Metabolic pathways, genomic alterations, and post-translational modifications in pulmonary hypertension and cancer as therapeutic targets and biomarkers - Zhang, Xiujin; Fu, Zhiqing; Wang, Haijun; Sheng, Li (Frontiers in Pharmacology, 2024)
Background: Pulmonary hypertension (PH) can lead to right ventricular hypertrophy, significantly increasing mortality rates. This study aims to clarify PH-specific metabolites and their impact on genomic and post-translational modifications (PTMs) in cancer, evaluating DHA and EPA’s therapeutic potential to mitigate oxidative stress and inflammation. Methods: Data from 289,365 individuals were analyzed using Mendelian randomization to examine 1,400 metabolites’ causal roles in PH. Anti-inflammatory and antioxidative effects of DHA and EPA were tested in RAW 264.7 macrophages and cancer cell lines (A549, HCT116, HepG2, LNCaP). Genomic features like CNVs, DNA methylation, tumor mutational burden (TMB), and PTMs were analyzed. DHA and EPA’s effects on ROS production and cancer cell proliferation were assessed. Results: We identified 57 metabolites associated with PH risk and examined key tumor-related pathways through promoter methylation analysis. DHA and EPA significantly reduced ROS levels and inflammatory markers in macrophages, inhibited the proliferation of various cancer cell lines, and decreased nuclear translocation of SUMOylated proteins during oxidative stress and inflammatory responses. These findings suggest a potential anticancer role through the modulation of stress-related nuclear signaling, as well as a regulatory function on cellular PTMs. Conclusions: This study elucidates metabolic and PTM changes in PH and cancer, indicating DHA and EPA’s role in reducing oxidative stress and inflammation. These findings support targeting these pathways for early biomarkers and therapies, potentially improving disease management and patient outcomes.